ChemInform Abstract: Solid State Structure of Bi(N3)3, Bi(N3)3·Solvates and the Structural Dynamics in the [Bi(N3)6]3‐ Anion. Issue 29 (1st July 2013) - Rosenstengel, Kati; Schulz, Axel; Villinger, Alexander
Abstract: Highly explosive Bi(N3 )3 is obtained by the reaction of BiF3 with Me3 SiN3 in MeCN under solvothermal conditions at 90—100 °C.